Local cooling reduces skin ischemia under surface pressure in rats: an assessment by wavelet analysis of laser Doppler blood flow oscillations - Jan, Yih-Kuen (2012)
The objectives of this study were to investigate the effects of local cooling on skin blood flow response to prolonged surface pressure and to identify associated physiological controls mediating these responses using wavelet analysis of blood flow oscillations in rats. Twelve Sprague Dawley rats were randomly assigned into three protocols, including pressure with local cooling (Δt= −10°C), pressure with local heating (Δt= 10°C), and pressure without temperature changes. Pressure of 700 mmHg was applied to the right trochanter area of rats for 3 hours. Skin blood flow was measured using laser Doppler flowmetry. The 3-hour loading period was divided into non-overlapping 30 min epochs for analysis of the changes of skin blood flow oscillations using wavelet spectral analysis. The wavelet amplitudes and powers of three frequencies (metabolic, neurogenic and myogenic) of skin blood flow oscillations were calculated. The results showed that after an initial loading period of 30 min, skin blood flow continually decreased in the conditions of pressure with heating and of pressure without temperature changes, but maintained stable in the condition of pressure with cooling. Wavelet analysis revealed that stable skin blood flow under pressure with cooling was attributed to changes in the metabolic and myogenic frequencies. This study demonstrates that local cooling may be useful for reducing ischemia of weight-bearing soft tissues that prevents pressure ulcers.